Les relations canado-américaines dans une ère d'incertitude - Doran, Charles (Études internationales, 1996)
The following treatment of U.S.-Canada relations begins with the Ottawa-Quebec nexus and its impact upon the connection with the United States. Then the analysis proceeds through bilateral relations. The essay concludes with a look at multilateral interactions from the focus of both Canada and the United States. Thus the analysis proceeds from the most specific to the most general, and from the most internalized to the most external. Concluding with a paradox, the argument of the essay is that despite the end of the Cold War and the disappearance of imminent external threat, uncertainty has never loomed larger in the relation of Canada to its southern neighbor, for all parts of Canada including Quebec, and for the Canadian polity as a whole.